The art of business value - Schwartz, Mark (Chief Information Officer) (IT Revolution, 2016)
Playful and thought-provoking, The Art of Business Value explores what business value means, why it matters, and how it should affect your software development and delivery practices. More than any other IT delivery approach, DevOps (and Agile thinking in general) makes business value a central concern. This book examines the role of business value in software and makes a compelling case for why a clear understanding of business value will change the way you deliver software.